(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
Culture is one of the influences on the products of architecture. It is common to say that architecture is a mirror of culture, Language, gestures and intellectual products are influenced by culture, The customs, traditions of a given society play an important role in some products architecture, These hidden aspects of physical products are subject to the traditions and customs of the society in which they exist, An example of these products was the "Architextile", which constituted an important aspect of the human civilization’s first production and since its creation to the human societies, as the human intertwined between the traditions and customs of the societies to which he belong and the product of his creations and is evident in architecture, The research discusses the subject of imitation strategies of traditions and customs", which has emerged in the distinctive architectural products of man and throughout the ages, Where many studies have touched on this output, but from many aspects, and did not shed light on the strategy of imitating the customs and traditions of the communities in which the production is located, Hence, the research problem emerged "the lack of comprehensiveness of previous studies of the role of the strategy of imitating traditions and customs in achieving the aesthetic, functional and performance dimensions of contemporary architextile, From the emergence of the research problem, the objective of the research was determined. Based on the previous studies (literary, historical and architectural), "a comprehensive theoretical framework was developed that illustrates the strategy of imitating traditions and customs and their role in achieving the aesthetic, functional and performance dimensions of contemporary architextile," The development of the main and secondary vocabulary, Then subtract and analyze the final findings and conclusions.